Fundamental science and medicine at the crossroads of life concept - A. K. Blbulyan (IRBIS LLC, 2022)
The laws of fundamental science dictate the rules of thinking. And the latter, in turn, form the methodology of science. With the discovery of the second law of thermodynamics, it became possible to approach the issues of the universe in a different way, in this case - to the issues related to organization of living matter. In this respect, the principle of elimination has been reflected at all levels of living matter being not only the achievement in cognition, but also a prospective motivation for our actions.